Recovering Intrinsic Pulsar Profile using a CLEAN- based Alogorithm for high precision Pulsar timimg - bathula, Adarsh (IISER Mohali, 2023)
Abstract will be available soon
embargo period
Keywords: Intrinsic; Pulsar; Alogorithm